2002
DOI: 10.2170/jjphysiol.52.553
|View full text |Cite
|
Sign up to set email alerts
|

Modulating Effects of the Menstrual Cycle on Cardiorespiratory Responses to Exercise under Acute Hypobaric Hypoxia.

Abstract: Anecdotal evidence, recently supported by scientific evidence, suggests that altitude training may offer advantages over sea-level (SL) training [1][2][3][4][5]. As a consequence, many elite athletes, female as well as male, now train at high altitude in an effort to enhance their SL performance. It is known that the menstrual cycle modulates thermoregulatory and cardiorespiratory responses, both at rest and during exercise, but it is not yet clear how this modulation is altered by moving to a higher altitude … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…This has also been observed in women during the menstrual cycle (42,45). Regarding Tb, our results show an increase on the day of estrus, similar to that previously .…”
Section: Estrous Cycle and V E Metabolism And Tbsupporting
confidence: 92%
“…This has also been observed in women during the menstrual cycle (42,45). Regarding Tb, our results show an increase on the day of estrus, similar to that previously .…”
Section: Estrous Cycle and V E Metabolism And Tbsupporting
confidence: 92%
“…Indigenous non-pregnant women residing at a high altitude had greater progesterone levels during the luteal phase of the menstrual cycle in comparison with women living at sea level [31]. Additionally, women exposed to acute hypobaric hypoxia showed higher plasma progesterone concentrations during the luteal phase than controls under normoxia [32]. …”
Section: Discussionmentioning
confidence: 99%
“…It is known that in both hypobaric and normobaric hypoxic environments, maximal oxygen uptake (VO 2max ) and anaerobic threshold (AT) decrease with reduction in inspired PO 2 , and that there is a consequent decrease in aerobic performance (Gavin et al1998;Koistinen et al 1995;Martin and O'Kroy 1993;Squires and Buskirk 1982;Takase et al 2002). On the other hand, McLellan et al (1990) reported that neither mean nor peak power output in a 30 s to 45 s Wingate test showed any change in hypoxia (10.8% O 2 ).…”
Section: Introductionmentioning
confidence: 99%